Innovative heuristics modeling for dynamic project cost control - Perumalsamy, Radhakrishnan; Natarajan, Jeyanthi (International Journal of Engineering and Technology, 2019)
Smart project management greatly improves the bottom line of the projects towards organizationâ€™s competitive edge. The dynamic nature of cost escalations of the various tasks of the project is a serious issue during project execution stage. Efficient project management is a complex process with an effort to execute the project within the budget provisions. The complexity increases when more number of tasks and longer duration of the project are involved. In this paper, a Particle Swarm optimization methodology is proposed and implemented to generate essential predictive analytics in maintaining optimal project cost performance.Â Â Â